THE PRINCIPLES OF ANTI-DISCRIMINATION AND PROTECTION OF MATERNAL RIGHTS OF FEMALE LABORERS VIEWED FROM THE PERSPECTIVE OF GENDER EQUALITY - Nurjannah S (Jurnal IUS Kajian Hukum dan Keadilan, 2013)
Anti-discrimination is also known by the term opportunity and equal treatment. The opportunity and equal treatment is a right of every citizen in all fields of life, whether economic, social, cultural, political and labor affairs. One of the most fundamental rights is the maternal right of female workers, including the right to menstruation leave, maternity leave, get social security in the form of care during childbirth and after childbirth, breast feeding and caring for the rights and child rearing. This research is to look at the law as the principles of truth and justice that is natural and universally applicable. This is consistent with normative legal research, the study of the principles of law or legal principles. On normative legal research, data processing activities to conduct systematize nature of the material written law. Systematizes means making a classification of materials written laws to facilitate the analysis and construction work. The principle of anti-discrimination and protection of workers’ rights maternal woman in Indonesia has been stated in the statutory provisions and refers to international conventions on human rights and the Convention on the Elimination of All Forms of Discrimination Against Women and ILO Convention No. 183 Year 2000 on Maternity Protection (ILO Convention on Maternity Protection). These rights include the right to menstruation leave, maternity leave, maternity leave, the right to bear the cost of the company or employer through labor social security, and the right feed and care for the child and the right of special treatment (affirmative action) in employment. However, long-time child care, it is not described in detail in the statutory provisions and arrangements delivered to the employer or the employer and the worker. This clause is felt still too discriminatory given that the rights of children to be treated and was raised by a mother (especially working mothers) marred. So we need a judicial review of Law No. 13 of 2003 relating to the protection of the rights of women workers as a form of maternal implementing anti-discrimination principle.Keywords: Anti-Discrimination, Protection of Workers, Rights Maternal